Legal Status of the Navigable Rivers of the Grand Duchy of Lithuania in the 16th–18th Centuries - Bedulskis, Rimantas (Lietuvos istorijos studijos, 2023)
The article examines the legal status of the navigable rivers of the Grand Duchy of Lithuania (further – GDL) in the 16th–18th centuries, based on Lithuanian Statutes, Sejm resolutions (constitutions), city privileges, other legal sources, and historiographical data. The problem of the content and usage of the term "navigable river" found in multilingual sources is examined. The study showed that this term contained two meanings: it indicated the physical characteristics of rivers and defined their legal status as a free path. In these rivers, it was forbidden to build any obstacles that make navigation difficult (fish traps, mill dams, or other barriers) and to collect new "unusual" customs duties. In the GDL’s law, the problem of shipping obstacles has been tried to solve in two ways: a) by specifying the obstacles to be removed physically and/or providing fines; b) by the mandatory installation of gates in fish traps and dams.